A machine learning based approach for DDos attack detection - Tahrim, Tasmiah; Sharan, MD Asif; Monsur, Meshaq; Hasan, MD Abid; Azad, Tanzina Binte (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.